Effect of experimental hyperthyroidism on CatSper1 and CatSper2 genes expression in the seminiferous tubules of BALB/c mice: An experimental study - Saeed Sadeghi; Mahdi Jalali; Mohamad Reza Nikravesh; Mojtaba Sankian (Shahid Sadoughi University of Medical Sciences, 2020)
Background: CATSPER 1 (Cation Channel Sperm Associated 1) and CATSPER2 channels have an important role in sperm motility. In this study, the effects of hyperthyroidism on Catsper1 and 2 genes of seminiferous tubules in mice testes were investigated. Objective: The present study was conducted to investigate the effect of hyperthyroidism on the expression of CATSPER1 and CATSPER2 genes in the seminiferous tubules of mice. Materials and Methods: This study was conducted on 20 BALB/C male mice divided into two groups - experimental and control. The experimental group was administered with 500 mg/l levothyroxine (L-thyroxine) liquid solution for two months for inducing hyperthyroidism, which was confirmed by radioimmunoassay. On the other hand, the control group was kept in animal houses under a normal condition. The implementation of real-time polymerase chain reaction and immunohistochemical studies was accomplished after the removal of the testes of the mice under anesthesia induced by chloroform. Results: Results showed that there was no significant difference in CATSPER1 (p = 0.45) and CATSPER2 (p = 0.34) gene expression between groups. At the same time, the color intensity showed no significant enhancement in the hyperthyroidism group (CATSPER1 p = 0.17 and CATSPER2 p = 0.22) as compared to the control group. Conclusion: Considering the key role of CATSPER in the molecular structure of the sperm, our findings showed that the hyperactivity of the thyroid gland has no significant effects on the function of these components. Therefore, it might be concluded that hyperthyroidism has no considerable effects on the seminiferous tubules.